Physical, Chemical, and Hedonic Characteristics of Mango Arumanis (Mangifera indica L.) Jelly Drink with Varied Carrageenan Addition as Gelling Agent - Siti Susanti; Asya Sabila Urai; Bhakti Etza Setiani; Anang Mohamad Legowo; Maela Rizky Kusumastuti (Journal of Agri-Food Science and Technology, 2025)
This study contributed to evaluate the effect of different concentrations of kappa carrageenan on the physicochemical and sensory properties of Arumanis mango (Mangifera indica L.) jelly drink. Kappa carrageenan, a sulphated polysaccharide extracted from red seaweed, is widely used in the food industry as a gelling, thickening, and stabilizing agent. Arumanis mango, known for its sweet taste and strong aroma, has limited natural pectin content, thus requiring additional hydrocolloids for gel formation. Four concentrations of kappa carrageenan (0.35%, 0.40%, 0.45%, and 0.50%) were tested using a Completely Randomized Design with five replications. Physicochemical parameters (syneresis, viscosity, pH and moisture content) and sensory attributes (texture, taste, aroma, color, and overall acceptance) were evaluated. Results showed that carrageenan concentration significantly (p<0.05) influenced all tested parameters. Increasing carrageenan levels enhanced viscosity and pH while reducing syneresis moisture content. Sensory analysis revealed that the 0.40% carrageenan treatment (P2) produced the most desirable texture and overall acceptability. This study highlights that the optimal carrageenan concentration ensures a balance between physicochemical stability and consumer preference, contributing new insight into the development of high-quality jelly drinks from local mango varieties.